2021
DOI: 10.5005/jp-journals-10071-23846
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Very Elderly Patients Admitted to the Intensive Care Unit: A Retrospective and Observational Study

Abstract: A bstract Background In this study, we aim to describe clinical features and outcomes of very elderly (85 years old or older) patients and provide information about predictors of mortality and factors associated with the length of hospital stay (LOS). Materials and methods We reviewed retrospectively the files of patients over 85 years old and older who were admitted to the intensive care unit (ICU) of our training and research hospital betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The requirement of vasopressors in elderly ICU patients is significantly associated with poor outcomes in this study, which is in agreement with earlier reports. 2 , 6 , 24 , 26 28 The mortality rate for intubated patients was 28.7%, whereas previous published reports reported mortality rates ranging from 20.3 to 51%. 25 Previous research has shown that the intubation and receipt of mechanical ventilation were associated with increased mortality in elderly ICU patients.…”
Section: Discussionmentioning
confidence: 98%
“…The requirement of vasopressors in elderly ICU patients is significantly associated with poor outcomes in this study, which is in agreement with earlier reports. 2 , 6 , 24 , 26 28 The mortality rate for intubated patients was 28.7%, whereas previous published reports reported mortality rates ranging from 20.3 to 51%. 25 Previous research has shown that the intubation and receipt of mechanical ventilation were associated with increased mortality in elderly ICU patients.…”
Section: Discussionmentioning
confidence: 98%
“…Anatomical and physiological changes due to aging pose a challenge for the anesthetic management of elderly patients. A decrease in physical capacity and an increase in the number of accompanying comorbidities are observed in elderly patients (1,4). Frailty is a state of vulnerability to stress factors due to a decrease in both physiological reserves and physical functions dependent on age.…”
Section: Sample Collection and Measurement Of Serum Levels Of Vitamin...mentioning
confidence: 99%
“…Frailty is present in approximately 10% of people over the age of 65 and 25-50% of people over the age of 85 (3,5). Frailty is likely to be common in geriatric patients undergoing surgery and has been strongly associated with increased perioperative morbidity and mortality in these patients (2)(3)(4)(5)(6)(7). The frailty index (FI) is a valuable criterion in the preoperative evaluation of patients undergoing geriatric surgery.…”
Section: Sample Collection and Measurement Of Serum Levels Of Vitamin...mentioning
confidence: 99%
See 2 more Smart Citations